d-electrons and superconductivity of transition metal oxides - Sergeeva, G.G. (Вопросы атомной науки и техники, 2001)
Some problems of the normal state of high temperature cuprate superconductors (HTS) with d-wave pairing are discussed. It is shown that: 1) at pseudogap temperature T* it occurs the dimensional crossover of the normal incoherent state to quasi 2D system of Cu O2 layers; 2) «naked holes» are bad quasiparticles for quasi 2D system with Jahn-Teller and mixed-valent Cu ions, with strong electron correlations and fluctuations, and with inherent strong p-d hybridization of copper and oxygen orbitals. Under these circumstances the holes are reduced to two types of the magneto-elastic polarons: the ferromagnetic bound polarons, which lead to forming of the stripes state, and antiferromagnetic Jahn-Teller-Zhang-Rice polarons which can form pairs and lead to the superconductivity.